$\begin{array}{1 1}\large\frac{1-(A)^n}{1-a} \\ \large\frac{1-(-a)^n}{1+a} \\\large\frac{1-(-a)^n}{1-a} \\ \large\frac{1+(-a)^n}{1+a} \\ \large\frac{1+(-a)^n}{1+a} \end{array} $

Want to ask us a question? Click here

Browse Questions

Ad |

0 votes

0 votes

- Sum of $n$ terms of a G.P=$S_n=a.\large\frac{1-r^n}{1-r}$ where first term=$a$ and common ratio=$r$

Given G.P is $1,-a,a^2,-a^3........$

In this G.P first term$=a=1$ and common ratio $=r=-a$

We know that sum of $n$ terms of a G.P.$=a.\large\frac{1-r^n}{1-r}$

$\therefore \:S_n=1.\large\frac{1-(-a)^n}{1-r}$

Ask Question

Take Test

x

JEE MAIN, CBSE, NEET Mobile and Tablet App

The ultimate mobile app to help you crack your examinations

...